Numerical and experimental design of a fuel heat exchanger for unmanned aerial vehicles, fabricable by additive manufacturing to enhance performance and mass efficiency - Topcu, Dincer; Gemici, Zafer (SPRINGER, 2025)
Additive manufacturing enables the production of complex geometries that are not feasible with conventional methods, offering significant potential for lightweight and efficient heat exchangers. This study investigates the hydraulic and thermal performance of a conventional unmanned aerial vehicle (UAV) fuel heat exchanger through both experimental measurements and computational fluid dynamics (CFD) simulations. Experimental tests were conducted at air velocities of 4-6 m s-1 to evaluate pressure drop and heat transfer characteristics. A validated CFD model was then used to explore alternative fin geometries optimized for additive manufacturing. Among the tested designs, the SD hole fin type demonstrated superior thermal performance with reduced mass. The optimized heat exchanger, featuring an integrated air hood and flow-directing plates, achieved a 6% improvement in heat transfer while reducing mass by approximately 200 g, corresponding to a 30% reduction compared to the existing cooler. The results highlight the potential of additive manufacturing to enhance both performance and mass efficiency in UAV thermal management systems.
Keywords: Additive manufacturing; Unmanned aerial vehicle; Fuel heat exchanger; Heat transfer; Pressure drop; Air-side fin; CFD; PRESSURE-DROP CORRELATIONS; LOUVERED FIN; Thermodynamics; Chemistry